Optimizing Maritime Logistics for Antarctic Research: A Hybrid Electric Fleet Approach with Adaptive Speed Selection - Parada-Daza, V (Taylor and Francis Ltd., 2025)
In the challenging environment of the Chilean Antarctic Territory, maritime logistics to support scientific research entail navigating through complex operational constraints, including harsh weather conditions and environmental sustainability considerations. This paper introduces a novel mixed integer bilinear programming model tailored for a fleet of hybrid electric ships that transport a single type of cargo, emphasising adaptive speed selection to enhance fuel efficiency and logistical efficacy. The model extends the traditional maritime inventory routing problem by incorporating energy-related constraints that reflect the hybrid propulsion system of the vessels. We leverage real-world data to explore diverse operational scenarios across different time horizons, unveiling strategies that significantly reduce fuel consumption while ensuring timely and reliable supply chain operations. Our findings contribute to the operational efficiency of maritime inventory routing and support the sustainable management of logistics in extreme conditions. The insights from this study may inform future developments in hybrid maritime transport systems, offering a scalable approach to optimise resource allocation and reduce environmental impact in logistics networks. © 2025 Informa UK Limited, trading as Taylor & Francis Group.